Application of Pegadaian Digital Service Application in Pawn Transactions at PT. Pegadaian (PERSERO) UPC Katamso Medan - Nurul Azmi, Syahfrilla Al risa; Dharma, Budi (Universitas Ibn Khaldun, 2023)
PT. Pegadaian (Persero) is a non-bank financial institution which is legally permitted to carry out credit financing on the basis of pawn law. PT. Pegadaian is currently carrying out transformation in the digital world by creating a web-based application called